Joyce's Araby and Yeats's Byzantium, 30.07- 03.08.2001. IASIL, Dublin, Irska - Gjurgjan, Ljiljana Ina (2001)
The paper looks into the way in which the two authors use the Orientalist symbols. For Yeats Byzantium symbolises the abstract, non- representational, synthetic art and is thus characteristic of his neo-Platonic attitude towards reality. This attitude is characteristic of all Yeats’s poetry, proclaiming that not only personal, but even national recuperation and spiritual decolonialization can be achieved solely through the aesthetic. On the other hand, Joyce uses the Orientalist motif as symbolic of the different, more sensual and pleasurable world the entrance into which is blocked by spiritual paralysis characteristic of colonial self- definition.